alguem poderia resolver por favor
Anexos:
![](https://pt-static.z-dn.net/files/d9a/100913716f34aa782fef78639361ca34.jpg)
Soluções para a tarefa
Respondido por
1
(a^3 - b^2) ^ (x+2)
[(-2)^3 - (-3)^2] ^ (-4+2)
(-8 - 9) ^ -2
-17 ^ -2
- 1/289
vitoriafj:
muito obrigadaa
Respondido por
1
(a^3 - b^2) ^ x+2
a= -2
b= -3
x= -4
(-2^3 - (-3)^2) ^ -4+2
(-8 - 9) ^ -2
-17 ^ -2
-0,00346 ← resultado
a= -2
b= -3
x= -4
(-2^3 - (-3)^2) ^ -4+2
(-8 - 9) ^ -2
-17 ^ -2
-0,00346 ← resultado
Perguntas interessantes
Inglês,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Música,
1 ano atrás